2020
DOI: 10.1007/s40279-020-01377-7
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Effects of Unilateral Strength and Skill Training: Modified Delphi Consensus to Establish Key Aspects of Cross-Education

Abstract: Background Cross-education refers to increased motor output (i.e., force generation, skill) of the opposite, untrained limb following a period of unilateral exercise training. Despite extensive research, several aspects of the transfer phenomenon remain controversial. Methods A modified two-round Delphi online survey was conducted among international experts to reach consensus on terminology, methodology, mechanisms of action, and translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 43 publications
1
55
1
1
Order By: Relevance
“…However, the effects of the unilateral AEL on the non-trained contralateral limb have not been explored. Nonetheless, it is well known that unilateral resistance exercise increases muscle strength of the contralateral non-trained homologous muscles, which is referred to as the cross-education or cross-transfer effect [ 1 , 2 , 3 , 15 , 40 ]. Green and Gabriel [ 40 ], in their review paper, reported that the magnitude of the increase in muscle strength for the contralateral non-trained limb ranged from 52 to 80% of that of the trained limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of the unilateral AEL on the non-trained contralateral limb have not been explored. Nonetheless, it is well known that unilateral resistance exercise increases muscle strength of the contralateral non-trained homologous muscles, which is referred to as the cross-education or cross-transfer effect [ 1 , 2 , 3 , 15 , 40 ]. Green and Gabriel [ 40 ], in their review paper, reported that the magnitude of the increase in muscle strength for the contralateral non-trained limb ranged from 52 to 80% of that of the trained limb.…”
Section: Discussionmentioning
confidence: 99%
“…According to the specialized literature, it is widely known that cross-education is specific to the homologous muscle group and the magnitude of the contralateral gains largely depends on those obtained ipsilaterally [ 2 , 15 ]. However, the extent of cross-education effects on heterologous muscles has not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Tseng et al [ 31 ] showed that the magnitude of cross-education effect on elbow flexor strength was similar (50 %) between ET and CT; however, the trained arm showed 50 % greater increase in maximal isometric contraction strength after ET than CT, inducing 50 % greater increase in elbow flexor strength of the non-trained arm after ET than CT. It has been reported that an intervention of 4–6 weeks is necessary to induce a cross-education effect [ 26 ]. Thus, the duration of the training period in the study by Tseng et al [ 31 ] might have been sufficient, but the training frequency (once a week) might not have been enough to maximize the cross-education effect.…”
Section: Introductionmentioning
confidence: 99%
“…Cross education is defined as the performance gain (i.e., transfer of strength and skills) in the untrained homologous muscle group after unilateral motor training, which has been shown for a wide range of motor tasks. Different changes within the nervous, muscle, and endocrine systems can explain the processes underlying the transfer of effects from training of the unaffected to the affected leg (10)(11)(12). Patients with TKA usually develop interlimb asymmetries (decrements in muscle size, strength, and voluntary activation) as a consequence of decreased mobilization before surgery and especially in the early post-operative phase (1,13).…”
Section: Introductionmentioning
confidence: 99%